Liquid Crystal-Reconfigurable Antenna Concepts for Space Applications at Microwave and Millimeter Waves. (3rd February 2009) - Gaebler, A.; Moessinger, A.; Goelden, F.; Manabe, A.; Goebel, M.; Follmann, R.; Koether, D.; Modes, C.; Kipka, A.; Deckelmann, M.; Rabe, T.; Schulz, B.; et al.
Abstract : Novel approaches of tunable devices for millimeter wave applications based on liquid crystal (LC) are presented. In the first part of the paper, a novel concept of a tunable LC phase shifter realized in Low Temperature Cofired Ceramics technology is shown while the second part of the paper deals with a tunable high-gain antenna based on an LC tunable reflectarray. The reflectarray features continuously beam scanning in between± 25 ∘ . Also first investigations on radiation hardness of LCs are carried out, indicating that LCs might be suitable for space applications.